Current and emerging treatment strategies for hair loss in women of color - U.R. Okereke, MD, MSCI; A. Simmons, MD; V.D. Callender, MD (Wolters Kluwer, 2019)
Hair loss is common in women of color, and is associated with significant psychosocial complaints. Early clinical recognition and prompt initiation of intervention with medical treatment is critical to halt the disease process. In this article, we review the clinical presentations of nonscarring and scarring alopecias in women of color, use of dermoscopy for early recognition of the disease process, and medical, procedural, and surgical interventions. In conditions that result in scarring alopecia, such as late-stage traction, frontal fibrosing, or central centrifugal cicatricial alopecia, patients may benefit from procedural interventions, such as hair transplantation, platelet rich plasma injections, low-level laser therapy, or scalp therapy. Keywords: Hair loss, alopecia, treatment, afro-textured hair, women of color, hair transplantation, hair restoration